2014
DOI: 10.1007/s10682-014-9734-7
|View full text |Cite
|
Sign up to set email alerts
|

Influences of geographic differentiation in the forewing warning signal of the wood tiger moth in Alaska

Abstract: Geographic Variation in the WarningSignals of the Wood Tiger Moth (Parasemia plantaginis; Arctiidae)Esitetään Jyväskylän yliopiston matemaattis-luonnontieteellisen tiedekunnan suostumuksella julkisesti tarkastettavaksi yliopiston Ylistönrinteellä, salissa YAA303 marraskuun 8. päivänä 2013 kello 12.Academic dissertation to be publicly discussed, Warning signals are not expected to be diverse because they are under stabilizing selection. This dissertation aims to study historic and contemporary selection mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 242 publications
(312 reference statements)
1
14
0
Order By: Relevance
“…Parasemia plantaginis forewing patterning is fairly similar to Grammia 's forewings, and it is reasonable to ask whether they have a protective function, aposematic or disruptive. In this regard, recent experiments by Hegna & Mappes () did not find evidence of disruptive function of forewings when moth dummies were presented on green background to predators. Instead, their results suggested that the forewing patterning is aposematic.…”
Section: Discussionmentioning
confidence: 83%
“…Parasemia plantaginis forewing patterning is fairly similar to Grammia 's forewings, and it is reasonable to ask whether they have a protective function, aposematic or disruptive. In this regard, recent experiments by Hegna & Mappes () did not find evidence of disruptive function of forewings when moth dummies were presented on green background to predators. Instead, their results suggested that the forewing patterning is aposematic.…”
Section: Discussionmentioning
confidence: 83%
“…The combination of black‐and‐white forewings with red or yellow hindwings may thus be an efficient learning cue for birds. In fact, birds readily avoid the forewing pattern of A. plantaginis (Hegna & Mappes, ).…”
Section: Discussionmentioning
confidence: 99%
“…The species occurs in the Holarctic, forming two distinct clades, one of which corresponds to P. plantaginis ssp. caucasica (Ménétries), with both male and female moths expressing ‘interrupted’ forewing pattern (Hegna & Mappes, ; Honma et al , ) and hindwing coloration varying from yellow to red (Fig. D).…”
Section: Introductionmentioning
confidence: 99%